2019
DOI: 10.1136/bmjopen-2018-027438
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HPV and other self-reported STI coinfections among sexually active Brazilian young adults: cross-sectional nationwide study

Abstract: ObjectivesTo analyse factors associated with genital human papillomavirus (HPV) and other self-reported sexually transmitted infection (STI) coinfections among women and men aged 16–25 years from Brazil.DesignA cross-sectional, nationwide, multicentre study.Setting119 primary healthcare centres between September 2016 and November 2017.Participants6388 sexually active young adults were enrolled by trained health professionals.Primary outcome measureGenital HPV and other self-reported STI coinfections.ResultsOf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
3
20
1
3
Order By: Relevance
“…Among women who reported HPV/coinfections, women with one secondary infection were predominant, primarily by N. gonorrhoeae and HIV. Despite being a study carried out in a population of Brazilian women, the results differ from those reported in our study [ 2 ]. A possible explanation may be the method used for STI detection used by Kops et al [ 2 ], which occurred through the participants' self-report and may not reflect the actual status of these STIs during the interview.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Among women who reported HPV/coinfections, women with one secondary infection were predominant, primarily by N. gonorrhoeae and HIV. Despite being a study carried out in a population of Brazilian women, the results differ from those reported in our study [ 2 ]. A possible explanation may be the method used for STI detection used by Kops et al [ 2 ], which occurred through the participants' self-report and may not reflect the actual status of these STIs during the interview.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies aiming to assess the prevalence of STIs in the general population are mainly focused on the identification of HIV and syphilis [ 15 – 17 ]. Despite the number of studies aiming to evaluate the prevalence of multiple STIs, only a few sought to assess the association between HPV and other STIs with the progression of cervical lesions [ 2 , 17 ]. Since there are currently more than 30 types of STIs worldwide and different methods of detecting these pathogens, we need to be careful in comparing studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A striking finding of this study was that less than one third of GPs interviewees stated that they often or always collect information on the sexual habits of 12–26 years’ girls and boys. It is worth mentioning that GPs should be aware of population groups at risk for unhealthy sex life habit since such behavior plays an important role in the process of high-risk HPV persistent infection for adolescents and young adults [ 20 , 21 , 22 ]. Therefore, it is important to know the adolescent’s sexual habits in order to prioritize preventive strategies and to develop educational campaigns that should be routinely conducted to prevent the spread of HPV.…”
Section: Discussionmentioning
confidence: 99%